Study and Analysis of Agriculture Bank Position in motivated Investment of Technologies ppropnate with Libyan: Environn1ent "applied study" - عبد الأمير الحسين د. سمير; ناصر حسین أ. جاسم (Dirasat in Economics and Business, 2004)
The Agriculture Bank was one of big financjal companies provide the financial to agri culture sector (farmers and far ming society) to investment in the agriculture utilities to provide the factors for this utility like equipments and tools, equipments of irrigation, seeds and fertilizers and other requirements of production. From all of these it wants to provide the aims of population transformation planing in provide self-sufficiency or decrease feeding gap by increasing the agriculture production. The Agriculture Bank has a position in motivated the investment in the technologies filed, because it is not financial state only but it has an important position in the development operation. This study aims to evaluate the position of agriculture bank in Benghazi city, starting from the aims drawing to it as a financial state aims to provide.